Alibaba Cainiao’s Smart green logistics strategy: Good for the earth, good for the business - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2021)
In November 2020, after the world’s largest online shopping festival, also known as Singles’ Day or “11.11 Global Shopping Festival” in China ended on a high note, the express delivery industry was again confronted with issues of burgeoning packaging waste and increasing carbon footprint from parcel deliveries. Cainiao Smart Logistics Network, a logistics arm of Alibaba Group, the largest e-commerce company in China, had been mitigating the impact caused by rapid e-commerce and logistic development. An e-commerce logistics platform, Cainiao led the industry to embark on nationwide green campaigns and launched digitalisation initiatives, including the introduction of e-shipping labels, smart packing, sorting, and parcel routing algorithms. On a broader scale, Cainiao had also built smart warehouses, and deployed robots and autonomous vehicles that contributed to lower ecological footprint. Yet, much remained to be done and at a significant cost. What else could Cainiao do to promote going green, keeping in mind that there was an economic cost associated with all such initiatives? In the discussion of the case, students will be able to evaluate how Cainiao, a smart logistics platform enabled by technology implements its smart, green logistics strategy while seeking to balance efficiency and economic profits. Additionally, students will analyse the ways in which companies can facilitate green logistics and identify opportunities to pursue sustainability across the entire supply chain.